Perbaikan Sifat Kimia Tanah pada Lahan Marginal untuk Meningkatkan Produksi Jagung melalui Teknik Olah Tanah Konservasi dan Pupuk Organik-Anorganik - Kusairi, David; Sunarti, Sunarti; Aswandi, Aswandi (CV. Eduartpia Publisher, 2023)
If marginal land is less productive, if it can be resolved, it can be used as productive land for agriculture. This study aims to analyze the effect of applying conservation tillage techniques and a combination of organic and inorganic fertilizers on soil chemical properties on marginal land and maize production. This research was conducted in Jambi Outer City District, Muaro Jambi Regency, Jambi Province, from January to April 2021 using a randomized block design with 2 treatments, namely doses of organic fertilizer and soil processing techniques. The first treatment has 5 levels, and the second treatment has 3 levels. There were 15 treatment combinations, each repeated 3 times. Parameters observed were corn plant height, weight of corn cobs, weight of dry shelled seeds, Soil pH, Soil C-Organic content, soil nitrogen content, soil phosphorus content, soil potassium content, exchange capacity cation, base saturation. The results showed that the application of conservation tillage techniques and a combination of organic and inorganic fertilizers had a significant effect on corn plant height 45 DAP, corn cob weight, soil pH, C-Organic soil, soil phosphorus content, soil potassium content, cation exchange capacity. Keyword: Conservation Soil, Organic Fertilizer, Soil Chemical Properties